Carcinogenicity of intermediate frequency magnetic field in Tg.rasH2 mice. Issue 3 (15th March 2019) - Nishimura, Izumi; Doi, Yuko; Imai, Norio; Kawabe, Mayumi; Mera, Yukinori; Shiina, Takeo
Abstract : Although the likelihood of exposure to leaking intermediate frequency magnetic fields (MFs) from electronic devices, such as induction‐heating and wireless power transfer systems, has increased, biological data assessing the health risks associated with human exposure remain insufficient. We examined the carcinogenicity of a 20 kHz MF, a typical frequency produced by induction‐heating cookers, using a transgenic rasH2 mouse model. Twenty‐five male and female CByB6F1‐Tg(HRAS)2Jic mice were exposed to a 0.20 mT, 20 kHz MF (22 h/day) or sham‐exposed for 26 weeks. As a positive control, 10 male and female rasH2 mice from the same batch were administered a single intraperitoneal injection of 75 mg/kg N ‐methyl‐ N ‐nitrosourea. A blinded histopathological evaluation was performed, and the same experiments were conducted twice, independently, to confirm the reproducibility of the results. Histopathological examination revealed that spontaneous neoplastic lesions, such as splenic hemangiosarcomas and gastric squamous cell papillomas, were less (1–3 per group) in the MF‐ and sham‐exposed groups. The frequency of the neoplastic lesions was not significantly different between the groups. Eight to ten mice in each positive‐control group exhibited malignant lymphoma. The outcomes were consistent between duplicated experiments, which indicates lack of carcinogenicity of 20 kHz MF in the rasH2 mouse model. Bioelectromagnetics. © 2019 The Authors. Bioelectromagnetics Published by Wiley Periodicals, Inc.